Healthcare Professionals' Attitudes and Practices According to Their Recommendations on Exercise during the First Trimester of Pregnancy: A Greek Cross-Sectional Study - Vasileios Daglas; Nikolaos Kostopoulos; Irina Mrvoljak-Theodoropoulou; Michalis Mitrotasios; Maria Dagla; Aikaterini Lykeridou; Evangelia Antoniou (MDPI AG, 2024)
Background: The aim of this study is to investigate healthcare professionals' attitudes and practices when it comes to their recommendations on exercise during the first trimester of pregnancy and to highlight the factors that influence or predict these attitudes. Methods: This cross-sectional study was conducted between January 2022 and March 2023, on a sample of 237 Greek healthcare professionals (midwives and obstetricians) employed in healthcare settings in Attica/Greece. In the statistical analysis, eight independent models of multivariate analyses of variance were conducted. Results: Only half of the participants (54.89%) report that they recommend exercise to pregnant women in the first trimester of pregnancy. The majority do not routinely recommend a specific frequency and duration of exercise. Participants who believe that exercise during pregnancy is of little benefit to pregnant women were less likely to recommend the following, in the first trimester of pregnancy: (a) exercise in general (p = 0.002), (b) resistance/muscle strengthening exercises (p = 0.039), (c) relaxation exercises (p = 0.002), and (d) a specific exercise duration (p = 0.011). Those who report being very familiar with the international guidelines are (a) more likely to recommend exercise in general (p = 0.013), as well as aerobic exercises (p = 0.023); (b) less likely to not recommend a specific frequency (p = 0.027); and (c) more likely to recommend a duration of 30-45 min of exercise in the first trimester (p = 0.017). Conclusions: I this study, a significant proportion of health professionals' attitudes appear to diverge from the recommendations set forth by international scientific bodies regarding exercise during pregnancy. Furthermore, health professionals' beliefs regarding the benefits of exercise during pregnancy, along with their familiarity with international guidelines, appear to influence their usual practices in recommending exercise during the first trimester of pregnancy to pregnant women.